Easy-to-operate single-sided adhesive super-soft high-thermal-conductivity gasket and preparation method thereof

By designing a combination of ultra-thin thermal conductive film and silicone thermal conductive gasket in high thermal conductive gaskets, the ratio of ceramic fillers and modifiers is optimized, and the existing high thermal conductive gaskets with high thermal conductivity are solved, and ultra-flexible high thermal conductive gaskets with high thermal conductivity, excellent compression and good operating performance are achieved.

CN119590059APending Publication Date: 2025-03-11SHANGHAI ALLIED PLASTIC IND

Patent Information

Application Number
CN202411431852.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing high-thermal gaskets have problems such as high hardness, powdering after aging, and oil seepage, which makes it impossible to effectively fill the air gap between the heating device and the heat sink, hindering heat transfer.

Method used

An easy-to-operate single-sided adhesive ultra-soft and high thermal conductivity gasket is designed. Through the combination of an ultra-thin thermal conductivity film and silicone thermal conductivity gasket, the ratio of ceramic fillers and modifiers is optimized to ensure thermal conductivity, compression and resilience, while improving operating performance.

Benefits of technology

While ensuring high thermal conductivity, it provides excellent compression and rebound, and has good operating performance, which is suitable for internal high heat dissipation devices.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of heat-conducting materials, in particular to an easy-to-operate single-sided adhesive super-soft high-heat-conducting gasket and a preparation method thereof. The ultrathin heat-conducting film is prepared from the following raw materials in parts by weight at least: 85-220 parts of ceramic filler, 10-50 parts of vinyl silicone oil, 1-10 parts of a cross-linking agent, 0.5-5 parts of a modifier, 0.1-2 parts of an inhibitor and 0.2-2 parts of a catalyst, and the ultrathin heat-conducting film is designed to be matched with a heat-conducting gasket, so that the provided product has excellent compressibility and rebound resilience on the premise of ensuring high heat-conducting property, and the service life of the ultrathin heat-conducting film is prolonged. Meanwhile, the operability is good, and the actual use requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal conductive materials, in particular to an easy-to-operate single-sided adhesive ultra-flexible high thermal conductive gasket and a preparation method thereof. Background Art

[0002] As the performance and functionality of electronic devices improve, the heat generated by the devices increases, making it particularly important to effectively dissipate, dissipate and cool the heat. For high-performance mobile products such as 5G smartphones and AR / VR devices, the installation space for heat dissipation components is limited due to the use of high-performance chips and highly integrated designs that pursue weight reduction. Therefore, the use of high thermal conductivity pads can bring better heat dissipation.

[0003] However, the high thermal conductive pads at this stage generally have the problems of high hardness, pulverization after aging, oil seepage, etc., and can not well fill the air gap between the heating device and the heat sink or the metal base, which will seriously hinder the transfer of heat between the contact surfaces. And the ultra-soft thermal conductive pad can well handle this kind of problem, it can make the contact surface better fully contact, and truly achieve face-to-face contact. For example, Chinese patent (authorization announcement number is CN115092920B) discloses graphene thermal conductive pad and preparation method thereof, specifically, thermal conductive fillers such as graphene are compounded with polymer materials to improve the compression performance of the graphene thermal conductive pad as a whole, but the operability for workers is faced with great problems, and the ultra-soft pad faces the poor properties such as low thermal conductivity, and poor operability, and is not suitable for the inside of high heat dissipation devices at this stage.

[0004] Therefore, how to ensure high thermal conductivity while having excellent compressibility and resilience of ultra-flexible thermal gaskets and allowing operators to have good operating performance is a technical challenge in the field of thermal conductive materials. Summary of the invention

[0005] In order to solve the above problems, the present invention provides an easy-to-operate single-sided adhesive ultra-soft high thermal conductivity gasket. By designing an ultra-thin thermal conductive film in combination with a silicone thermal conductive gasket, the provided product has excellent compressibility and resilience while ensuring high thermal conductivity, and at the same time has good operability to meet actual use needs.

[0006] On the one hand, the present invention provides an easy-to-operate single-sided adhesive ultra-flexible high thermal conductive gasket, comprising an ultra-thin thermal conductive film and a silicone thermal conductive gasket; in parts by weight, the raw materials for preparing the ultra-thin thermal conductive film include at least: 85-220 parts of ceramic filler, 10-50 parts of vinyl silicone oil, 1-10 parts of cross-linking agent, 0.5-5 parts of modifier, 0.1-2 parts of inhibitor, and 0.2-2 parts of catalyst.

[0007] As a preferred technical solution, the raw materials for preparing the silicone thermal conductive gasket include at least 150-300 parts by weight of a high thermal conductivity modified mixed filler, 2-15 parts of vinyl silicone oil, 0.1-5 parts of methyl silicone oil, 0.1-1 parts of a cross-linking agent, 0.1-2 parts of an inhibitor, and 0.2-2 parts of a catalyst.

[0008] As a preferred technical solution, the mass ratio of the ceramic filler to the modifier is 100:(0.5-5).

[0009] As a preferred technical solution, the modifier is selected from at least one of octyltrimethoxysilane, dodecyltrimethoxysilane, n-octyltriethoxysilane, vinyltrimethoxysilane, and hexamethyldisilazane, preferably octyltrimethoxysilane or hexamethyldisilazane.

[0010] As a preferred technical solution, the ceramic filler is selected from at least one of aluminum oxide, aluminum nitride, magnesium oxide and zinc oxide.

[0011] Preferably, the ceramic filler is a combination of aluminum oxide and zinc oxide.

[0012] Preferably, the mass ratio of aluminum oxide to zinc oxide is (80-200):(5-20), preferably (80-150):(5-10), and more preferably (100-150):5.

[0013] Preferably, the alumina is selected from at least one of angular alumina, spherical alumina, and single crystal alumina.

[0014] Preferably, the particle size of the angular alumina or spherical alumina is 1-70 μm, preferably including at least one of 1 μm, 2 μm, 5 μm, 10 μm, 20 μm, 40 μm, and 70 μm.

[0015] Preferably, the particle size of the single crystal aluminum oxide is 0.3-5 μm, preferably including at least one of 0.3 μm, 1.5 μm, 3 μm, and 5 μm.

[0016] Preferably, the particle size of the zinc oxide is 0.5-3 μm, preferably including at least one of 0.5 μm, 1 μm, and 3 μm.

[0017] Preferably, the particle size of the aluminum nitride is 2-150 μm, preferably including at least one of 2 μm, 10 μm, 20 μm, 80 μm, 100 μm, 120 μm, and 150 μm.

[0018] As a preferred technical solution, the particle size of the ceramic filler is 0.1-20 μm.

[0019] Preferably, the ceramic filler is a combination of single crystal alumina, spherical alumina and zinc oxide.

[0020] Preferably, in parts by weight, the ceramic filler includes 20 parts of 0.3 μm single crystal alumina (Bai Tu), 40 parts of 2 μm spherical alumina (Bai Tu), 60 parts of 20 μm spherical alumina (Bai Tu) and 5 parts of 0.5 μm zinc oxide (Bai Tu).

[0021] As a preferred technical solution, the particle size of the high thermal conductivity modified mixed filler is 0.1-200 μm.

[0022] As a preferred technical solution, the raw materials for preparing the high thermal conductivity modified mixed filler at least include a mixed ceramic filler and a modifier, and the mass ratio of the mixed ceramic filler to the silane modifier is 100:(0.2-5).

[0023] As a preferred technical solution, the mixed ceramic filler includes at least: single crystal alumina, spherical alumina, zinc oxide, and aluminum nitride.

[0024] Preferably, in parts by weight, the mixed ceramic filler includes: single crystal alumina (1.5 μm, 5 parts; 5 μm, 10 parts), spherical alumina (1 μm, 5 parts; 2 μm, 15 parts; 40 μm, 30 parts), zinc oxide (0.5 μm, 3 parts), and aluminum nitride (20 μm, 5 parts; 120 μm, 27 parts).

[0025] As a preferred technical solution, the silane modifier is selected from at least one of octyltrimethoxysilane, dodecyltrimethoxysilane, n-octyltriethoxysilane, vinyltrimethoxysilane, and hexamethyldisilazane, preferably octyltrimethoxysilane or hexamethyldisilazane.

[0026] As a preferred technical solution, the preparation method of the high thermal conductivity modified mixed filler is: fill the mixed ceramic filler into the modification equipment, then add the modifier, close the modification equipment to make its cavity airtight, first use 10-200rpm to stir for 0.5-90min, after stirring, open the modification equipment, manually scrape off the raised powder, close the modification equipment again, use 150-500rpm to stir for 0.5-30min, after stirring, pour out the modified filler, bake in an oven at 50-170℃ for 0.5-24h, take out and cool after baking to obtain the high thermal conductivity modified mixed filler.

[0027] As a preferred technical solution, the mass ratio of vinyl silicone oil to cross-linking agent in the ultra-thin thermal conductive film is (20-30):(3-7), preferably 25:(4-6).

[0028] As a preferred technical solution, the vinyl content in the vinyl silicone oil is 0.08-10wt%.

[0029] Preferably, the vinyl silicone oil is selected from at least one of double-ended vinyl silicone oil, single-ended vinyl silicone oil and side-chain vinyl silicone oil, and has a viscosity (25° C., ASTM D2196) of 20-1000 mPa·s.

[0030] Preferably, the vinyl silicone oil is single-ended vinyl silicone oil (Guangdong Chensi New Material Technology Co., Ltd., cx-352m, vinyl content 0.18wt%).

[0031] As a preferred technical solution, the methyl silicone oil is at least one of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecamethylcyclohexasiloxane, and has a viscosity (25° C., ASTM D2196) of 20-1000 mPa·s.

[0032] Preferably, the methyl silicone oil is hexamethylcyclotrisiloxane.

[0033] As a preferred technical solution, the crosslinking agent is terminal hydrogen-containing silicone oil, side hydrogen-containing silicone oil or a mixture of one or more of terminal and side hydrogen-containing silicone oils, and has a viscosity (25° C., ASTM D2196) of 10-5000 mPa·s.

[0034] Preferably, the cross-linking agent is a combination of terminal hydrogen-containing silicone oil (Shanghai Jingri, brand DH007) and side hydrogen-containing silicone oil (Shanghai Jingri, brand H020), and the mass ratio of the terminal hydrogen-containing silicone oil to the side hydrogen-containing silicone oil is (3-8):1, preferably 5:1.

[0035] As a preferred technical solution, the inhibitor is acetylene cyclohexanol.

[0036] As a preferred technical solution, the catalyst is a platinum catalyst.

[0037] The present invention optimizes the raw material selection and addition amount control of the ultra-thin thermal conductive film so that it is tightly bonded with the organic silicon thermal conductive gasket, thereby ensuring the comprehensive performance of the easy-to-operate single-sided adhesive ultra-soft high thermal conductive gasket after compounding. In particular, the mass ratio of the vinyl silicone oil and the cross-linking agent in the ultra-thin thermal conductive film is controlled to be (20-30): (3-7) to ensure the compression resilience of the thermal conductive gasket after compounding, while avoiding the situation where the ultra-thin thermal conductive film and the thermal conductive gasket are not tightly bonded after curing.

[0038] Furthermore, the present invention optimizes the ceramic filler in the ultra-thin thermally conductive film to be a combination of angular alumina, spherical alumina or single crystal alumina and zinc oxide, further controls the particle size of the ceramic filler in the ultra-thin thermally conductive film to be 0.1-20 μm, and cooperates with the high thermal conductivity modified mixed filler introduced into the silicone thermally conductive gasket including single crystal alumina, spherical alumina, zinc oxide, and aluminum nitride to ensure that the thermal conductivity of the thermally conductive gasket after compounding is above 8-10 W / mk.

[0039] In addition, the present invention controls the introduction of octyltrimethoxysilane or hexamethyldisilazane as a modifier into the ultra-thin thermal conductive film, and controls the mass ratio of the ceramic filler to the modifier to be 100:(0.5-5), so that the ceramic filler is evenly dispersed in the silicone system, achieves good compatibility between the organic phase and the inorganic material, and reduces the difficulty of subsequent compounding with the silicone thermal conductive gasket.

[0040] Another aspect of the present invention provides a method for preparing an easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket, which comprises at least the following steps:

[0041] (1) Preparation of ultra-thin thermal conductive films;

[0042] (2) adding vinyl silicone oil, methyl silicone oil, a crosslinking agent, and an inhibitor into a stirring kettle, then adding a high thermal conductivity modified mixed filler and stirring and mixing, then adding a catalyst and stirring and mixing again to obtain a rubber compound;

[0043] (3) The mixed rubber is extruded onto an ultra-thin thermal conductive film, and then calendered and baked to obtain an easy-to-operate single-sided adhesive ultra-soft high thermal conductive gasket.

[0044] As a preferred technical solution, the preparation method of the ultra-thin thermal conductive film is: put the modifier, vinyl silicone oil, cross-linking agent, and inhibitor into a stirring kettle, stir and mix, add ceramic filler and catalyst, stir and mix, put into a three-roll mill for kneading, add a diluent after kneading, stir and mix, spray it on the base film, bake and roll it to obtain the ultra-thin thermal conductive film.

[0045] As a preferred technical solution, the diluent is a silicone diluent, preferably RH-2001-0.65, Runhe.

[0046] As a preferred technical solution, the amount of the diluent added is 0.5-50% based on the mass of the material after kneading.

[0047] As a preferred technical solution, the preparation method of the ultra-thin thermal conductive film is as follows: put the modifier, vinyl silicone oil, cross-linking agent and inhibitor into a stirring kettle, stir at 10-200rpm for 0.1-5min, add ceramic filler and catalyst, stir at 50-500rpm for 0.5-30min, maintain vacuum during stirring, put into a three-roller machine for kneading after stirring and mixing, control the thickness to 5-50μm, knead three times, add a diluent after kneading, stir at 50-500rpm for 0.5-10min, and then spray on the base film, the spraying thickness is controlled to 10-100μm, control the drying oven temperature to 100-140℃, and the baking time is 10-60min. After baking, roll up to obtain the ultra-thin thermal conductive film.

[0048] As a preferred technical solution, the step (2) is specifically as follows: vinyl silicone oil, methyl silicone oil, crosslinking agent and inhibitor are added into a stirring kettle, and then a high thermal conductivity modified mixed filler is added and stirred at 10-50 rpm for 5-30 min, and the temperature is kept at 20-30° C. and vacuum is turned on during stirring; then a catalyst is added and stirred at 30-50 rpm for 1-30 min, and the temperature is kept at 10-20° C. and vacuum is turned on during stirring, and after scraping the wall, stirring is continued at 5-20 rpm for 10-120 min to obtain a rubber compound, and the temperature is kept at 10-20° C. and vacuum is turned on during stirring.

[0049] As a preferred technical solution, the baking treatment time in step (3) is 30-100 minutes, the temperature is 100-140° C., and the calendering thickness is 0.3-5 mm.

[0050] The easy-to-operate single-sided adhesive ultra-soft high thermal conductivity gasket provided by the present invention has a hardness of up to shore00 5-25°, and a compression rebound rate of more than 80%. It is sticky on one side and easy to operate, and has a high market promotion value.

[0051] Beneficial Effects

[0052] 1. The present invention provides an easy-to-operate single-sided adhesive ultra-soft high thermal conductivity gasket. By designing an ultra-thin thermal conductive film in combination with a silicone thermal conductive gasket, the provided product has excellent compressibility and resilience while ensuring high thermal conductivity, and at the same time has good operability to meet actual use requirements.

[0053] 2. The present invention optimizes the raw material selection and addition control of the ultra-thin thermal conductive film to ensure a tight bond between the film and the silicone thermal conductive gasket, thereby ensuring the comprehensive performance of the easy-to-operate single-sided adhesive ultra-soft high thermal conductive gasket after compounding. In particular, the mass ratio of the vinyl silicone oil and the cross-linking agent in the ultra-thin thermal conductive film is controlled to be (20-30): (3-7) to ensure the compression resilience of the thermal conductive gasket after compounding, while avoiding the situation where the ultra-thin thermal conductive film and the thermal conductive gasket are not tightly bonded after curing.

[0054] 3. The present invention optimizes the ceramic filler in the ultra-thin thermally conductive film to be a combination of angular alumina, spherical alumina or single crystal alumina and zinc oxide, further controls the particle size of the ceramic filler in the ultra-thin thermally conductive film to be 0.1-20 μm, and cooperates with the high thermal conductivity modified mixed filler introduced into the silicone thermally conductive gasket, including single crystal alumina, spherical alumina, zinc oxide, and aluminum nitride, to ensure that the thermal conductivity of the thermally conductive gasket after compounding is above 8-10 W / mk.

[0055] 4. The present invention controls the introduction of octyltrimethoxysilane or hexamethyldisilazane as a modifier into the ultra-thin thermal conductive film, and controls the mass ratio of the ceramic filler to the modifier to be 100:(0.5-5), so that the ceramic filler is evenly dispersed in the organosilicon system, achieves good compatibility between the organic phase and the inorganic material, and reduces the difficulty of subsequent compounding with the organosilicon thermal conductive gasket.

[0056] 5. The easy-to-operate single-sided adhesive ultra-soft high thermal conductivity gasket provided by the present invention has a hardness of up to shore00 5-25°, while the compression rebound rate can be maintained at more than 80%. It is single-sided adhesive and easy to operate, and has a high market promotion value. DETAILED DESCRIPTION

[0057] Example 1

[0058] Embodiment 1 of the present invention provides, on the one hand, an easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket, comprising an ultra-thin thermal conductive film and an organic silicon thermal conductive gasket; by weight, the raw materials for preparing the ultra-thin thermal conductive film include: 125 parts of ceramic filler, 25 parts of vinyl silicone oil, 5 parts of cross-linking agent, 0.5 parts of modifier, 0.1 parts of inhibitor, and 0.5 parts of catalyst. By weight, the raw materials for preparing the organic silicon thermal conductive gasket include: 200 parts of high thermal conductivity modified mixed filler, 5 parts of vinyl silicone oil, 1 part of methyl silicone oil, 0.5 parts of cross-linking agent, 0.1 parts of inhibitor, and 0.2 parts of catalyst.

[0059] The modifier is octyltrimethoxysilane.

[0060] In parts by weight, the ceramic filler includes 20 parts of 0.3 μm single crystal alumina (Bai Tu), 40 parts of 2 μm spherical alumina (Bai Tu), 60 parts of 20 μm spherical alumina (Bai Tu) and 5 parts of 0.5 μm zinc oxide (Bai Tu).

[0061] The raw materials for preparing the high thermal conductivity modified mixed filler include a mixed ceramic filler and a modifier, and the mass ratio of the mixed ceramic filler to the silane modifier is 100:1.

[0062] In parts by weight, the mixed ceramic filler includes: single crystal alumina (1.5 μm, 5 parts; 5 μm, 10 parts), spherical alumina (1 μm, 5 parts; 2 μm, 15 parts; 40 μm, 30 parts), zinc oxide (0.5 μm, 3 parts), and aluminum nitride (20 μm, 5 parts; 120 μm, 27 parts).

[0063] The silane modifier is octyltrimethoxysilane.

[0064] The preparation method of the high thermal conductivity modified mixed filler is as follows: fill the mixed ceramic filler into the modification equipment, then add the modifier, close the modification equipment to make its cavity airtight, first stir at 100 rpm for 20 minutes, open the modification equipment after stirring, manually scrape off the raised powder, close the modification equipment again, stir at 300 rpm for 10 minutes, pour out the modified filler after stirring, bake in an oven at 150° C. for 3 hours, take out and cool after baking to obtain the high thermal conductivity modified mixed filler.

[0065] The vinyl silicone oil is a single-ended vinyl silicone oil (Guangdong Chensi New Material Technology Co., Ltd., cx-352m, vinyl content 0.18wt%).

[0066] The methyl silicone oil is hexamethylcyclotrisiloxane.

[0067] The cross-linking agent is a combination of terminal hydrogen-containing silicone oil (Shanghai Jingri, brand DH007) and side hydrogen-containing silicone oil (Shanghai Jingri, brand H020), and the mass ratio of the terminal hydrogen-containing silicone oil to the side hydrogen-containing silicone oil is 5:1.

[0068] The inhibitor is acetylene cyclohexanol.

[0069] The catalyst is a platinum catalyst.

[0070] Embodiment 1 of the present invention provides, on the other hand, a method for preparing an easy-to-operate single-sided adhesive ultra-flexible high thermal conductive gasket, comprising the following steps:

[0071] (1) Preparation of ultra-thin thermal conductive films;

[0072] (2) adding vinyl silicone oil, methyl silicone oil, a crosslinking agent, and an inhibitor into a stirring kettle, then adding a high thermal conductivity modified mixed filler and stirring and mixing, then adding a catalyst and stirring and mixing again to obtain a rubber compound;

[0073] (3) The mixed rubber is extruded onto an ultra-thin thermal conductive film, and then calendered and baked to obtain an easy-to-operate single-sided adhesive ultra-soft high thermal conductive gasket.

[0074] The preparation method of the ultra-thin thermal conductive film is as follows: a modifier, vinyl silicone oil, a cross-linking agent and an inhibitor are put into a stirring kettle, stirred at 50 rpm for 3 minutes, a ceramic filler and a catalyst are added, stirred at 200 rpm for 3 minutes, a vacuum is maintained during the stirring process, and after stirring and mixing, the mixture is put into a three-roller machine for kneading, the thickness is controlled to be 10 μm, and kneading is performed three times. After kneading, a diluent is added, stirred at 200 rpm for 50 minutes, and then sprayed on a base film, the spraying thickness is controlled to be 20 μm, the drying oven temperature is controlled to be 120° C., the baking time is 60 minutes, and the ultra-thin thermal conductive film is rolled up after baking.

[0075] The diluent is an organosilicon diluent, model RH-2001-0.65, Runhe.

[0076] The added amount of the diluent is 1% based on the mass of the material after kneading.

[0077] The step (2) is specifically as follows: vinyl silicone oil, methyl silicone oil, crosslinking agent and inhibitor are added into a stirring kettle, and then a high thermal conductivity modified mixed filler is added and stirred at 10 rpm for 10 min, and the temperature is kept at 25° C. and vacuum is turned on during the stirring; then a catalyst is added and stirred at 30 rpm for 5 min, and the temperature is kept at 17° C. and vacuum is turned on during the stirring, and after scraping the wall, stirring is continued at 10 rpm for 120 min to obtain a rubber mixture, and the temperature is kept at 17° C. and vacuum is turned on during the stirring.

[0078] The baking time in step (3) is 40 minutes, the temperature is 120° C., and the rolling thickness is 0.3 mm.

[0079] Example 2

[0080] Embodiment 2 of the present invention provides an easy-to-operate single-sided adhesive ultra-flexible high thermal conductive gasket and a preparation method thereof. Its specific implementation method is the same as that of Embodiment 1, except that, by weight, the raw materials for preparing the ultra-thin thermal conductive film include: 125 parts of ceramic filler, 25 parts of vinyl silicone oil, 2 parts of cross-linking agent, 0.5 parts of modifier, 0.1 parts of inhibitor, and 0.5 parts of catalyst.

[0081] Example 3

[0082] Embodiment 3 of the present invention provides an easy-to-operate single-sided adhesive ultra-flexible high thermal conductive gasket and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that, by weight, the raw materials for preparing the ultra-thin thermal conductive film include: 125 parts of ceramic filler, 25 parts of vinyl silicone oil, 8 parts of cross-linking agent, 0.5 parts of modifier, 0.1 parts of inhibitor, and 0.5 parts of catalyst. After curing, the ultra-thin thermal conductive film and the thermal conductive gasket will not be tightly bonded.

[0083] Example 4

[0084] Example 4 of the present invention provides an easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket and a preparation method thereof. Its specific implementation method is the same as that of Example 1, except that, by weight, the raw materials for preparing the silicone thermal conductive gasket include: 150 parts of high thermal conductivity modified mixed filler, 5 parts of vinyl silicone oil, 1 part of methyl silicone oil, 0.8 parts of cross-linking agent, 0.1 parts of inhibitor, and 0.2 parts of catalyst.

[0085] Performance Testing Methods

[0086] The thermal conductivity, hardness and compression rebound rate of the easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket provided in the embodiment of the present invention are tested. The test method is as follows. The test results are shown in Table 1.

[0087] (1) Thermal conductivity: measured according to ASTM D 5470-17 using Taiwan Ruiling LW-9389 interface material thermal resistance and thermal conductivity measuring device (at 25°C).

[0088] (2) Hardness: measured according to ASTM D2240 using a shore 00 durometer (at 25°C).

[0089] (3) Compression rebound rate: measured using a rapid compression tester (at 25°C) according to standard ASTM D575, compression rate: 20 mm / min, pressure maintained for 10 min, thickness measured after 20 min of pressure release, and compression rebound rate calculated based on the formula (compression rebound rate = (thickness after rebound - compressed thickness) / compressed thickness * 100%).

[0090] Table 1

[0091] Thermal conductivity (W / (m*K)) Hardness (Shore 00) Rebound rate Example 1 9.6 18 84% Example 2 9.5 12 60% Example 3 9.8 24 92% Example 4 8.5 20 87%

Claims

1. An easy-to-operate single-sided adhesive ultra-soft high thermal conductivity gasket, characterized in that: Includes ultra-thin thermal conductive film and silicone thermal conductive pad; By weight, the raw materials for preparing the ultra-thin thermal conductive film include at least: 85-220 parts of ceramic filler, 10-50 parts of vinyl silicone oil, 1-10 parts of cross-linking agent, 0.5-5 parts of modifier, 0.1-2 parts of inhibitor, and 0.2-2 parts of catalyst.

2. The easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket according to claim 1, characterized in that: By weight, the raw materials for preparing the silicone thermal conductive gasket include at least: 150-300 parts of high thermal conductivity modified mixed filler, 2-15 parts of vinyl silicone oil, 0.1-5 parts of methyl silicone oil, 0.1-1 parts of cross-linking agent, 0.1-2 parts of inhibitor, and 0.2-2 parts of catalyst.

3. The easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket according to claim 2, characterized in that: The mass ratio of vinyl silicone oil to cross-linking agent in the ultra-thin thermal conductive film is (20-30): (3-7).

4. The easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket according to claim 3, characterized in that: The vinyl content of the vinyl silicone oil is 0.08-10 wt %.

5. The easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket according to claim 4, characterized in that: The cross-linking agent is one or a mixture of terminal hydrogen-containing silicone oil, side hydrogen-containing silicone oil or terminal side hydrogen-containing silicone oil.

6. The easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket according to claim 5, characterized in that: The mass ratio of the ceramic filler to the modifier is 100:(0.5-5).

7. The easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket according to claim 6, characterized in that: The modifier is selected from at least one of octyltrimethoxysilane, dodecyltrimethoxysilane, n-octyltriethoxysilane, vinyltrimethoxysilane and hexamethyldisilazane.

8. The easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket according to claim 7, characterized in that: The ceramic filler is selected from at least one of angular alumina, spherical alumina, single crystal alumina, aluminum nitride, magnesium oxide, and zinc oxide.

9. The easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket according to claim 8, characterized in that: The methyl silicone oil is at least one of hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecamethylcyclohexasiloxane.

10. A method for preparing an easy-to-operate single-sided adhesive ultra-flexible high thermal conductivity gasket according to any one of claims 2 to 9, characterized in that: At least the following steps are included: (1) Preparation of ultra-thin thermal conductive films; (2) adding vinyl silicone oil, methyl silicone oil, a crosslinking agent, and an inhibitor into a stirring kettle, then adding a high thermal conductivity modified mixed filler and stirring and mixing, then adding a catalyst and stirring and mixing again to obtain a rubber compound; (3) The mixed rubber is extruded onto an ultra-thin thermal conductive film, and then calendered and baked to obtain an easy-to-operate single-sided adhesive ultra-soft high thermal conductive gasket.

Citation Information

Patent Citations

  • Graphene thermal conductive pads and their preparation methods

    CN115092920B

  • Thermal-conductive silicon sheet and manufacturing method thereof

    CN102555331A

  • High-heat-conductivity high-compression wet-viscous-state heat-conducting gasket and preparation thereof

    CN104163016A

  • Thermally conductive composite silicone rubber sheet

    JP2014193598A

Cited By

  • Easy-to-operate single-sided adhesive super-soft high-thermal-conductivity pad and preparation method therefor

    WO2026081477A1